Teks Tutur Prabu Santanu: Analisis Struktur Dan Fungsi - Apriyanti, Ni Nyoman; Sutama, Putu; Mulyawati R, Tjok Istri Agung (Humanis, 2016)
The study regarding to the text of Tutur Prabu Santanu was aimed to analyze its structure and function. The theory used in this study were the theory of structure and function proposed by Luxemburg, Teeuw as well as Wellek & Warren. The methods used in this study were qualitative method as well as informal method. In addition, note-taking technique, analytic descriptive technique and deductive inductive technique were used in this study. The result of the study revealed the structure and function of the text of Tutur Prabu Santanu. The structure of the text is narrative consisting of incident, plot, character and characterization, setting, theme, as well as mandate. The function of the text is as medium of education consisting of ethics and philosophical learning as well as medium of entertainment.